The construction of moral autonomy: Jane Loevinger's ego development theory contribution - Branco, Maria Luísa (Paidéia (Ribeirão Preto), 2003)
Since the beginnings of occidental reflection, moral autonomy was considered as a sign of human maturity. According to the cognitive-developmental tradition, the construction of moral autonomy is mainly a process of separation- individuation. The ego developmental theory of Jane Loevinger, combining the cognitive developmental and the psychoanalytic approaches, propose an understanding of moral autonomy as the result of a separation-inclusion movement. Therefore a more adequate comprehension of this phenomenon emerges, associated to a frame of socio-affective maturity.